IL-4 Production by Group 2 Innate Lymphoid cells Promotes Food Allergy by Blocking Regulatory T cell Function - Rivas, Magali Noval (J Allergy Clin Immunol, 2016)
BACKGROUND: Food allergy is a major health issue, but its pathogenesis remains obscure. Group 2 innate lymphoid cells (ILC2) promote allergic inflammation. However their role in food allergy is largely unknown. OBJECTIVE: We sought to investigate the role of ILC2 in food allergy. METHODS: Food allergy-prone mice with a gain of function mutation in the IL-4 receptor a chain (Il4raF709) were orally sensitized with food allergens and the ILC2 compartment was analyzed. The requirement for ILC2 in food allergy was investigated using Il4raF709, IL-33 receptor deficient (Il1rl1(−/−)), IL-13 (Il13(−/−)) and IL-4 (Il4(−/−)) deficient mice and by adoptive transfers of in vitro-expanded ILC2. Direct effects of ILC2 on regulatory T (Treg) cells and mast cells were analyzed in co-culture experiments. Treg cell control of ILC2 was assessed in vitro and in vivo. RESULTS: Food allergic Il4raF709 mice exhibit increased numbers of ILC2. IL-4 secretion by ILC2 contributes to the allergic response by reducing allergen-specific Treg cells and activating mast cells. IL-33 receptor deficiency in Il4raF709Il1rl1(−/−) mice protects against allergen sensitization and anaphylaxis while reducing ILC2 induction. Adoptive transfer of WT and Il13(−/−) but not Il4(−/−) ILC2 restored sensitization in Il4raF709 Il1rl1(−/−) mice. Treg cells suppress ILC2 in vitro and in vivo. CONCLUSION: IL-4 production by IL-33-stimulated ILC2 blocks the generation of allergen-specific Treg cells and favors food allergy. Strategies to block ILC2 activation or the IL-33:IL-33R pathway may lead to innovative therapies in food allergy.